Agitation-Induced Aggregation of Lysine- And Interchain Cysteine-Linked Antibody-Drug Conjugates - Johann, Florian; Wöll, Steffen; Winzer, Matthias; Gieseler, Henning (Journal of Pharmaceutical Sciences, 2024)
Drug conjugation to an antibody can affect its stability, which depends on factors such as the conjugation technique used, drug-linker properties, and stress encountered. This study focused on the effects of agitation stress on the physical stability of two lysine (ADC-K) and two interchain cysteine (ADC-C) conjugates of an IgG1 monoclonal antibody (mAb) linked to either ∼4 MMAE or DM1 payloads. During agitation, all antibody–drug conjugates (ADCs) exhibited higher aggregation than the mAb, which was dependent on the conjugation technique (aggregation of ADC-Ks > ADC-Cs) and drug-linker (aggregation of ADCs with MMAE > ADCs with DM1). The aggregation propensities correlated well with higher self-interaction, hydrophobicity, and surface activity of ADCs relative to the mAb. The intermediate reduced mAb (mAb-SH) showed even higher aggregation than the final product ADC-Cs. However, blocking mAb-SH's free thiols with N-ethylmaleimide (NEM) strongly reduced its aggregation, suggesting that free thiols should be minimized in cysteine ADCs. Further, this study demonstrates that a low-volume surface tension method can be used for estimating agitation-induced aggregation of ADCs in early development phases. Identifying liabilities to agitation stress and their relationship to biophysical properties may help optimize ADC stability.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Antibody–drug conjugate(s) (ADC); Conjugation; Developability; High-throughput technology(s); Monoclonal antibody(s); Physical stability; Protein aggregation